If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -4y = -5y Solving 9 + -4y = -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 9 + -4y + 5y = -5y + 5y Combine like terms: -4y + 5y = 1y 9 + 1y = -5y + 5y Combine like terms: -5y + 5y = 0 9 + 1y = 0 Add '-9' to each side of the equation. 9 + -9 + 1y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 1y = 0 + -9 1y = 0 + -9 Combine like terms: 0 + -9 = -9 1y = -9 Divide each side by '1'. y = -9 Simplifying y = -9
| 41+13x=37+8x+8 | | 0,1x-10=30 | | 5(3w+7)=-32 | | X^2=1.93 | | 4534543534534+4353434534= | | x(x-5)=176 | | (x-5)(x+4)=(x+7)(x-6) | | 3w+7=-6.4 | | 2k=-f-t | | 7-2x(x+4)=14+5x | | t=2k-f | | p=b+2d | | 3x*4x=600 | | 3x*4X=24 | | 7x+21y=28 | | 2x+4=-8-4x | | 2x-x+30=80 | | 2x*5+6=3 | | 2x*11=3 | | 750*1300= | | 14*2x+24*8-9=52*13+121*11 | | 90x^2-97xy+21y^2=0 | | 5678=10131213 | | 8x-6x+3=2 | | 2b+7=b+13 | | 15x+21y=261 | | 9v+27=-2(v+3) | | F(x-1)=10x-6 | | 55=9x | | 14+n=-9 | | 2x-(2+3)=5x | | 3x+15x-2x+3=15x+1x+3 |